PREPARATION AND IN VITRO EVALUATION OF SELF-NANO EMULSIFYING DRUG DELIVERY SYSTEMS OF KETOPROFEN - WANNAS, ALI N.; ABDUL-HASAN, MAZIN THAMIR; MOHAMMED JAWAD, KRAR KADHIM; RAZZAQ, INAS F. ABDUL (International Journal of Applied Pharmaceutics, 2023)
Objective: The aim of this study was to formulate, evaluate and characterise nanoemulsion formulation containing a lipophilic drug, Ketoprofen. Methods: Nanoemulsion formulations composed of oil, surfactant, co-surfactants and Ketoprofen were prepared. In all formulations, the percent of surfactants, as well as oil, was varied while the amount of Ketoprofen kept constant. Solubility studies were conducted to select the oil, surfactant and cosurfactant. Phase diagrams were constructed using the aqueous phase titration method. Formulations were selected from the phase diagrams. The prepared nanoemulsions were subjected to different thermodynamic stability tests. Results: Following optimization, the F7 formula (10% oil, 3:1 surfactant to co-surfactant) was thermodynamically stable, with a droplet size of 105 nm and a zeta potential of-26.21 mV. In vitro release study showed that the drug release pattern from formulations F5, F6, F7, F8, F9 and F10 was higher than that of F1, F2, F3 and F4. Conclusion: The present work demonstrates that the nanoemulsion is a promising drug delivery system approach for the enhancement of solubility and dissolution rate of Ketoprofen.